Voluntary Codes of Conduct for Multinational Corporations - Sethi, S. Prakash (Business ethics quarterly, 2006)
This issue of Business Ethics Quarterly offers a special forum incorporating a select group of papers that were presented at the First International Conference on “Voluntary Codes of Conduct for Multinational Corporations: Promises and Challenges,” held at the Zicklin School of Business, Baruch College, City University of New York, on May 12–15, 2004. The conference was organized by the International Center for Corporate Accountability (ICCA), Inc., and was co-sponsored by the Zicklin Center for Business Ethics Research of The Wharton School, University of Pennsylvania, and the World Bank’s World Bank Institute. Additional support was provided by a number of major corporations, academic institutions, and nongovernment organizations.